UPAYA PEMERINTAH DAERAH DALAM MENINGKATKAN TRANSPARANSI ANGGARAN DAERAH DI KOTA SEMARANG TAHUN 2016-2017 - Sujud Baitullaah; A Taufik (Journal of Politic and Government Studies, 2019)
This research was conducted to explain the efforts of the regional government in increasing regional budget transparency in the city of Semarang. This study uses a qualitative-descriptive research methodology because this research describes phenomena relating to current and experienced situations, attitudes and views that are present at the moment, the relationship between variables contradicts two or more conditions, the effect on a condition, and the difference between facts. This study is conducted by asking for information to the primary subject, namely the source and the main informant and the secondary subject, as an additional source of data in strengthening the data. The data then explains the efforts made by the Semarang City Government in increasing regional budget transparency as basic services as a condition for implementing good good governance with the principle of public information disclosure. The results of the study show that the Semarang city government always strives for improvements to increase budget transparency to the public. The Relationship of Budget Transparency with Public Information Openness, encourages the government to establish a legal basis regarding the guidelines for managing public information and documentation within the Semarang city government. In addition, it also explains the authority, problems, supporting and inhibiting factors, efforts, achievements and reforms, support for superiors, and relations between institutions in all ways to improve regional budget transparency. In the future, the Semarang city government needs to optimally and consistently improve regional budget transparency. Bringing up new innovations and fostering civil apparatus so that it becomes the best governance process and results. Keywords: Efforts, Public Information Openness, Budget Transparency, Semarang City Government